2021
DOI: 10.1111/ijfs.15418
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Bifidobacterium longum 51A cells by spray drying and its incorporation in acerola (Malpighia emarginata) pulp powder

Abstract: Market of functional foods grows intensely, such as of fruit juice containing probiotics. However, the survival of the microorganism can be compromised by the low pH of such matrix, and the way of minimizing this acid stress is the use of microencapsulation techniques such as by spray drying. In this study, three formulations were tested for the encapsulation of Bifidobacterium longum 5 1A , and the viability was evaluated during storage after the atomization process and after addition in acerola pulp powder. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The results showed that B. brevis cells not only survived as they also grew when in the GIT of children. Costa et al [ 187 ] showed that encapsulated Bifidobacterium longum 5 1A for bacterial protection during atomisation. In addition, the cells were protected from the acidity of acerola pulp.…”
Section: From the Physiology Of Production To The Processing Of The P...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that B. brevis cells not only survived as they also grew when in the GIT of children. Costa et al [ 187 ] showed that encapsulated Bifidobacterium longum 5 1A for bacterial protection during atomisation. In addition, the cells were protected from the acidity of acerola pulp.…”
Section: From the Physiology Of Production To The Processing Of The P...mentioning
confidence: 99%
“…Costa et al [ 187 ] showed that encapsulated Bifidobacterium longum 5 1A for bacterial protection during atomisation. In addition, the cells were protected from the acidity of acerola pulp.…”
Section: From the Physiology Of Production To The Processing Of The P...mentioning
confidence: 99%